PERAN GREEN TRUST DALAM MEMEDIASI PENGARUH GREEN PRODUCT PERCEPTION TERHADAP GREEN REPURCHASE INTENTION - Cahyani, Ni Luh Tiwi Hari; Wardana, I Made (E-Jurnal Manajemen, 2017)
Of the research aims to determine the effect of green trust and green product perception towards green repurchase intention on Ultrajaya products in Denpasar. T otal of 100 respondents were included in the study using purposive sampling method as the method of data collection . Selected samples have fulfilled all the criteria that have been determined. The data collection is done by distributing questionnaires using 5 point scale to measure likert 12 indicators where the indicators lowered to the questionnaire in the study. T his study use confirmatory factor analysis techniques and path analysis. The results showed that the variables green trust, capable of mediating green product perception influence of the green repurchase intention. These results prove that the trust can reinforce positive perceptions of consumers towards a product which raises the intention to repurchase.
Keywords: green trust, green product perception, green repurchase intention